2018
DOI: 10.1128/msphere.00047-18
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Domains of Highly Pathogenic Viral Fusion Proteins Exhibit Trimeric Association In Vitro

Abstract: Many important human pathogens are enveloped viruses that utilize membrane-bound glycoproteins to mediate viral entry. Factors that contribute to the stability of these glycoproteins have been identified in the ectodomain of several viral fusion proteins, including residues within the soluble ectodomain. Although it is often thought to simply act as an anchor, the transmembrane domain of viral fusion proteins has been implicated in protein stability and function as well. Here, using a biophysical approach, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…The TMDs of both EBOV GP and the SARS-CoV S proteins have been shown to exhibit monomer-trimer-hexamer oligomerization equilibrium when analyzed in isolation by SE-AUC [128]. Analysis of the EBOV GP MPER and TMDs using NMR revealed that both regions appear to be continuous helices independent of the pH, with a turn in between the two adjacent regions [129], similar to the MPER-TMD HIV structure discussed previously [75][76][77].…”
Section: Other Class I Viral Fusion Proteinssupporting
confidence: 59%
“…The TMDs of both EBOV GP and the SARS-CoV S proteins have been shown to exhibit monomer-trimer-hexamer oligomerization equilibrium when analyzed in isolation by SE-AUC [128]. Analysis of the EBOV GP MPER and TMDs using NMR revealed that both regions appear to be continuous helices independent of the pH, with a turn in between the two adjacent regions [129], similar to the MPER-TMD HIV structure discussed previously [75][76][77].…”
Section: Other Class I Viral Fusion Proteinssupporting
confidence: 59%
“…More importantly, our results show the important role of TM-TM interactions in the stability of the viral fusion protein on a global level. Utilizing TM-TM interactions to disrupt fusion protein function may also extend beyond paramyxoviruses, as we have recently shown that TM-TM interactions occur for fusion proteins of the families Coronaviridae, Rhabdoviridae, Orthomyxoviridae, and Filoviridae (40). These studies further broaden our understanding of the hydrophobic TM domain and demonstrate their functional role beyond serving as a hydrophobic membrane anchor.…”
Section: Discussionmentioning
confidence: 79%
“…Studies of several viral fusion proteins have shown that the transmembrane domain (TMD) is critical for driving fusion events (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). For HeV, previous work has shown that TMD interactions within the F protein trimer help preserve the metastable prefusion conformation and play a role in fusion promotion (29)(30)(31). More specifically, these findings suggest that HeV F TMD interactions are needed to stabilize the heptad repeat B (HRB) domains that form the stalk of the protein prior to triggering fusion (Fig.…”
mentioning
confidence: 99%